Compliance Control of a Cable-Driven Space Manipulator Based on Force–Position Hybrid Drive Mode - Runhui Xiang; Hejie Xu; Xinliang Li; Xiaojun Zhu; Deshan Meng; Wenfu Xu (Aerospace)
Multi-cable cooperative control is essential for cable-driven space manipulators to achieve in-orbit services such as fault spacecraft maintenance, fuel injection, on-orbit assembly, and orbital garbage removal. To prevent the cables from becoming slack or excessively tight, the force in each cable must be distributed appropriately. The force distribution among different cables requires real-time adjustments; otherwise, the system may become unstable. This paper proposes a compliance control method based on the force–position hybrid drive mode to address the challenges of multi-cable cooperative control. Firstly, the mapping relationship between the cable space and the joint space of the cable-driven space manipulator is established. Then, the force mapping relationship for this structure is derived. The control scheme categorizes the cables into two types: active-side cables and antagonistic-side cables. Position control and force control are implemented separately, significantly reducing the computational requirements and enhancing the overall performance of the control system. Finally, the feasibility of the proposed algorithm is demonstrated through simulations and compared with the PID control method. When tracking the same trajectory, the proposed method reduces the tracking error by 49.14% and the maximum force by 58.58% compared to the PID control method, effectively addressing the problem of force distribution in multi-rope coordinated control.